The unified equation by the Proportion 19 (-1:3) - Cameron, Vinoo (International Journal of Applied Mathematical Research, 2013)
As mankind is created in the image of a creator, the mathematical continuum is understandably connected, not by “Strings”, but by rational coordinates of mathematics. That is what this manuscript is all about; the rationalization of the natural expanse of mathematics and the stark reality of -1. The section on the mathematical PI (?) clearly proves the -1 constriction of 4-1. Definition of the Unified Theorem: “The ascension and expansion of all space (and mass) is curved, spiral and warped because of the -1 zero inverse primordial constriction of all space by -1. 4-(1) =+3). Bounded space is inverse at -1, a non-collapsible curve. The value of -1 is -1 for numbers and 0.5/60(1/120) for non-linear space. The minus 1 is manifested at proportion 19 as a composite of the of the values 9 and 10, both by numbers and prime angle (1:3). The proof of -1 is and has always been in the mathematical Pi (?), corrected trigonometry, and the spiral curved ascension of Prime numbers.” This proof is clearly stated under the section for the “mathematical Pi (?) where the author has clearly proven -1 by theorem.” This manuscript has been preceded by several manuscripts on Prime numbers, -1 and Prime number 19 that show the unified mathematics as a consequence of a -1 Vedic zero, and the overall -1 ( 4-3) . As the treatise on the Unified Theorem, this is all written by simple theorem .This manuscript completely disregards current mathematical theory with regard to non- linear mathematics as irrelevant to mathematics. The clear assertion is that the -1 Vedic zeros is the correct zero, but that the current null zero is in error. The inverse curved value off-set of -1 is the value that precedes the +1 value, and it is clearly stated by this author that mathematically a curve cannot ever be collapsed to null. There is no logical compromise in this regard. Essentially and mathematically the author validates the primordial -1, and the absolute primordial value of 360 as not being an arbitrary value, and the inverse constriction of the horizons by 4-1=3(-1/4)*4=-1.This translates into a rotation of 1/3 from 90 degrees to 120 degrees, which defines 360 as (90):*1*4=4 versus (90):*0.75*4 = 3 offset at 360. See the diagram. We have also shown that the locus site for the -1 constriction of all space by trigonometry and prime numbers is the prime 19 gap, represented  by the numbers (9), 19, (10) and the set 18 (19) 20 which is a -1 tangent set. We have also shown that the correct zero offset is not the current null zero, but the Vedic-1 zero, (not understood as such by the Vedic people) The author has clearly unified the mathematics of prime numbers, space, the mathematical Pi, and trigonometry under -1, Vedic zero, Prime 19(9, 10) as the prime (1:3) modulator of space. The basic root of the unified mathematics is also based on the Vedic zero, as is expressed herein the 1:3 ascension of prime numbers and the Pythagoras theorem at ). Each of the unification in trigonometry, prime numbers, and mathematical Pi (?) is discussed separately.